Forensic sexual assault examination and genital injury: is skin color a source of health disparity? - Sommers, Marilyn S. (2008)
PURPOSE: The study objectives were to (1) estimate the frequency, prevalence, type, and location of anogenital injury in black and white women after consensual sex and (2) investigate the role of skin color in the detection of injury during the forensic sexual assault examination. METHODS: A cross-sectional descriptive design was used with 120 healthy volunteers who underwent a well-controlled forensic examination after consensual sexual intercourse. RESULTS: Fifty-five percent of the sample had at least 1 anogenital injury after consensual intercourse; percentages significantly differed between white (68%) and black (43%) participants (P = .02). Race/ethnicity was a significant predictor of injury prevalence and frequency in the external genitalia but not in the internal genitalia or anus. However, skin color variables—lightness/darkness–, redness/greenness–, and yellowness/blueness–confounded the original relationship between race/ethnicity and injury occurrence and frequency in the external genitalia, and 1 skin color variable—redness/greenness —was significantly associated with injury occurrence and frequency in the internal genitalia. CONCLUSIONS: Although differences exist in anogenital injury frequency and prevalence between black and white women, such differences can be more fully explained by variations in skin color rather than race/ethnicity. Clinical recommendations and criminal justice implications are discussed.